ARIA‐EAACI statement on severe allergic reactions to COVID‐19 vaccines – An EAACI‐ARIA Position Paper. Issue 6 (15th June 2021) - Klimek, Ludger; Jutel, Marek; Akdis, Cezmi A.; Bousquet, Jean; Akdis, Mübeccel; Torres, Maria J; Agache, Ioana; Canonica, G. Walter; Del Giacco, Stefano; O'Mahony, Liam; Shamji, Mohamed H.; Schwarze, Jürgen; et al.
Abstract: Further to the approval of the Coronavirus disease 2019 (COVID‐19) vaccine BNT162b2, several severe anaphylaxis cases occured within the first few days of public vaccination. An investigation is taking place to understand the cases and their triggers. The vaccine will be administered to a large number of individuals worldwide and there are raising concerns that severe adverse events might occur. With the current information, the European Academy of Allergy and Clinical Immunology (EAACI) states its position for the following preliminary recommendations that are to be revised as soon as more data emerge. To minimize the risk of severe allergic reactions in vaccinated individuals, it is urgently required to understand the specific nature of the reported severe allergic reactions, including the background medical history of the individuals affected and the mechanisms involved. To achieve this goal, all clinical and laboratory information should be collected and reported. Mild and moderate allergic patients should not be excluded from the vaccine as this could have a significant impact on reaching the goal of population immunity. Healthcare practitioners vaccinating against COVID‐19 are required to be sufficiently prepared to recognize and treat anaphylaxis properly with the ability to administer adrenaline. Further to vaccine administration, a mandatory observation period of at least 15 minutes should be followed for all individuals. The current data have not shown any higher risk for patients suffering from allergic rhinitis or asthma, and this message should be clearly stated by physicians to enable our patients to trust the vaccine. More than 30% of the population suffers from allergic diseases and the benefit of the vaccination clearly outweighs the risk of severe COVID‐19 development.